THE EFFECTIVENESS OF PROVIDING COMPLEMENTARY THERAPY OF TURMERIC AND KENCUR HERBAL MEDICINE TO POSTPARTUM MOTHERS TO INCREASE BREAST MILK VOLUME IN THE WORKING AREA OF NORTH TAPIN HEALTH CENTER - Yunisa Dzul Hidayani; Winda Maolinda; Dede Mahdiyah (Ananda - Health & Education Foundation, 2023)
Background: Giving breast milk to babies is the best method of feeding. Exclusive breastfeeding coverage in Midwife Mandiri Midwife Independent Practice is still below the target; this can be caused by insufficient milk production. Asitri oil is a substance that can increase milk production, which is found in Asitri oil in turmeric and kencur Objective: Testing the effect of giving Jamu Turmeric and Kencur on increasing the volume of breast milk in postpartum women in the working area of the North Tapin Health Center. Methods: The type of research used in this study is quasi-experimental research. The sample consisted of 10 people divided into 2 (intervention and control groups). The intervention group was given turmeric and kencur therapy once a day, while the control group did not receive therapy. The analysis bivariate was performed bivariate analysis using a paired t-test. Results: Bivariate analysis based on age showed that all ten respondents (100%) were in the non-risk age range, namely 22 to 32 years. Based on postpartum days, most respondents from the two groups were on the third day with a total of 5 people, which was a percentage of 50%—tested data normal distribution. The results of the bivariate analysis showed a p-value of 0.000 which means less than an α value of 0.05 so that there was an effect of giving turmeric and kencur herbs on the smoothness of breastfeeding in postpartum mothers in the working area of the North Tapin Health Center. Conclusion: There was an increase in the volume of breast milk after being given turmeric and kencur herbs as big 120 ml during seven days, and the administration of turmeric and kencur herbs was effective in increasing the volume of breast milk in postpartum women in the working area of the Tapin Utara Health Center, Tapin Regency.